The holy grail of authentication. (December 2015) - Watts, Steve
Abstract : Two-factor authentication (2FA) has been about for much longer than you think. For a decade or more we have been used to being issued with a card reader (in essence a hardware token device) to use with our bank card and Personal Identification Number (PIN) when looking to complete our Internet banking transactions. And 2FA technology has, over the past year or so, been employed by seven of the 10 largest social networking sites (including Facebook, Twitter and LinkedIn) as their authentication measure of choice. 1